New perspectives on stress and negative emotions: Positive effects on adolescent learning, memory, and mental health - Jiawei Gao; Bohao Liu (PLoS ONE, 2025)
Background Negative emotions have long been regarded as detrimental to learning and memory, while the potential benefits of moderate stress remain underexplored. This study investigates how moderate stress influences adolescent learning and memory, advocating for an assessment of emotions to provide novel theoretical insights into adolescent mental health. Methods We recruited 53 middle school students and established a murine stress model. Behavioral tests and physiological indicators were systematically analyzed to evaluate the effects of varying stress intensities on learning, memory, and psychological states. Methods included acute stress tests, short-term memory assessments, and measurements of HPA axis hormone levels. Results The moderate stress group exhibited significantly better memory performance than the control group, whereas the high-stress group showed marked memory decline. Murine experiments revealed that moderate stress enhanced learning efficiency and was associated with normal HPA axis hormone regulation, supporting the complexity of stress effects. Conclusions Moderate stress can enhance adolescent learning and memory, challenging traditional views of stress as purely negative. Theoretically, moderate stress may activate adaptive mechanisms and improve cognitive function, offering a new framework for mental health interventions. These findings underscore the importance of balanced stress management in educational practices and psychological strategies.